Let's Entertain : life's guilty pleasures. - Halbreich, Kathy; Portland Art Museum, Oregon; Musée national d'art moderne, Centre Georges Pompidou, Parijs; Museo Rufino Tamayo, Mexico City; Miami Art Museum, Miami; Blair, Dike; Busch, Akiko; Davis, Susan G.; Dietz, Steve; Duncan, Emma; Gamson, Joshua; Ilesanmi, Olukemi; et al. (Minnesota : Walker Art Center, 2000)
Pierson, Jack ; Gursky, Andreas ; Wearing, Gillian ; Land, Peter ; Sherman, Cindy ; Cattelan, Maurizio ; McCarthy, Paul ; Koons, Jeff ; Warhol, Andy ; Hirst, Damien ; et al.
Let's entertain, Walker Art Center, Minnesota, February 12 - April 30, 2000
kunstcatalogus